Location, Working Capital, Corporate Governance, and Profitability: The Case of Indonesian Manufacturing Firms - Irene Rini Demi Pangestuti; Komang Yuli Pridarsanti; Robiyanto Robiyanto (International Journal of Business and Society, 2021)
This study scrutinizes the effect of location, working capital and corporate governance toward return on assets (ROA) in Indonesian manufacturing firms. 61 manufacturing firms listed on the Indonesia Stock Exchange were taken as samples in this study. The results show that location does not affect manufacturing firms’ profitability. Furthermore, this study proves that working capital management, as measured by current ratio (CR) and quick ratio (QR), has a positive and significant influence on return on assets (ROA), but cash ratio (CR) and the cash conversion cycle does not have a significant influence on return on assets (ROA). This study also found that the Good Corporate Governance Index (GCGI) has a positive and significant influence on return on assets (ROA) in Indonesian manufacturing firms.